Panopticonism dalam Media Massa (Analisis Wacana Berita Kasus Pemerkosaan Yn yang ditayangkan pada Program AIMAN Kompas TV Mei 2016) - Muhammad Ravi Ramadhan (Jurnal Kriminologi Indonesia, 2017)
This study discusses about the informative role of mass media that could be utilized as anappliance to control attitute and behavior of the society. The informative role could be definedas a form of specific criminal action including the sanctions that could ensnare all involvedperpretrators, while mass media used for the discussion is an investigation coverage, whichwas aired by Kompas TV. This study aims to explain about the application of panopticonismconcept through mass media. As previous research only focused to the discussion about massmedia role in controlling the criminal forms, but they did not explain further about the role ofmass media, which potentially could be utilized to control attitute and behavior of the society.Whereas, criminal representation through media generates discourse to deliver messagesto the public. Because most of criminal reporting on mass media do not only show aboutcronological information, but also the sanctions and policies that could ensnare all involvedperpetrators. With the result, through the informative role of mass media it could be expectedto generate impressions regarding surveillance and disciplinary action to the public.